The Effect of Competency Certification on the Working Conditions of Indonesia's Workers - Pabiangan, Netty (Ann Publisher, 2024)
This research discusses competency certification, which is official recognition for individuals who have met specific competency standards in a particular field or profession. This certification ensures that a person has abilities, knowledge, and skills by applicable industry or professional standards. Through certification, individuals can demonstrate that they have passed an objective assessment process and meet the requirements of the authorized certification body. This study uses a qualitative descriptive method with a literature research approach, focusing on secondary data analysis from scientific journals, articles, books, and relevant research reports. The results of the literature analysis show that competency certification significantly influences the quality of working conditions in Indonesia's workforce. This certification has been proven to improve the skills and knowledge of the workforce, which has an impact on increasing productivity and work efficiency. Certified workers generally get roles better suited to their abilities, a better work environment, and higher rewards and wages. In addition, competency certification also improves occupational well-being and safety by enhancing understanding of safety procedures and reducing the risk of work accidents. Overall, competency certification not only contributes to improving workers' quality of life but also creates a better and safer work environment, thereby enhancing the overall productivity and efficiency of the workforce.